2014
DOI: 10.1017/jns.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

Increasing volume of food by incorporating air reduces energy intake

Abstract: Major challenges with weight management using weight-loss diets include hunger and rapid consumption of food, both of which lead to poor owner compliance. The aim of the present study was to determine the effect of increasing volume, by incorporating air, into dry expanded food, on satiety in dogs. Three studies have been performed. The first study aimed to measure the effect of volume of food on meal duration in dogs fed at their maintenance energy requirement. The purpose of the second study was to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…However, prior to the start of each study, all dogs had been offered both foods to familiarise them. On test days, consumption kinetics was assessed through repeated short-term food exposure, using a modification of a protocol previously described [20, 22]. Briefly, each dog was offered 110 kcal/kg 0.75 for 15 min at 08:30 (1 st meal) and again at 09:30 (2 nd meal), and then offered food ad libitum for 15 min at both 10:30 (3 rd meal) and 11:30 (4 th meal).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, prior to the start of each study, all dogs had been offered both foods to familiarise them. On test days, consumption kinetics was assessed through repeated short-term food exposure, using a modification of a protocol previously described [20, 22]. Briefly, each dog was offered 110 kcal/kg 0.75 for 15 min at 08:30 (1 st meal) and again at 09:30 (2 nd meal), and then offered food ad libitum for 15 min at both 10:30 (3 rd meal) and 11:30 (4 th meal).…”
Section: Methodsmentioning
confidence: 99%
“…Instead, the group size used was equivalent to that used in previous studies assessing VFI and palatability [20, 22]. For the VFI studies, the primary outcome measure of interest was the amount of energy consumed (expressed both as KJ and Kcal per kg of MBW), whilst secondary outcomes included the weight of food consumed (in grams), and also BW (in kg) measured before and after each protocol (as described above).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low energy density diets have been suggested to improve pet owner's compliance, limit hunger signs and begging behaviours in dogs and cats on weight loss therapy (German, 2016). Common dietary strategies, in order to reduce energy density in pet diets, include increasing the volume of food by producing bigger, aerated kibbles (Serisier et al, 2014), increasing water content (Alexander et al, 2014), or to increase the inclusion of dietary fibre from non-digestible carbohydratebased plant materials (De Godoy et al, 2013;German et al, 2010b;Hours et al, 2016). Although dietary fibre is not a required nutrient in feline nutrition, the inclusion of optimal amounts of indigestible material in the diet allows a proper intestinal peristalsis and gut physiology (Kienzle et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…A study to determine the effect of increasing dietary volume by incorporating air into dry expanded dog food reported that increasing dietary volume decreased energy intake ( 13 ) . The dilution of dietary energy density by the addition of fibre has also been suggested as a strategy to reduce energy intake in dogs, although such studies have produced conflicting results.…”
mentioning
confidence: 99%